A review of coxiellosis (Q fever) and brucellosis in goats and humans: implications for disease control in smallholder farming systems in Southeast Asia - Burns, RJL; Le, KK; Siengsanun-Lamont, J; Blacksell, SD (Elsevier, 2023)
Coxiella burnetii and Brucella spp. are pathogenic bacteria that can cause large-scale outbreaks in livestock. Furthermore, these infectious agents are capable of causing zoonotic infections and therefore pose a risk to the close relationship between farm households and their livestock, especially goats. A review of seroprevalence studies of Coxiella burnetii and Brucella spp. in domestic goats demonstrated large differences in the total number of samples tested in different regions and countries. This review aims to provide information on coxiellosis (Q fever in humans) and brucellosis in goats concerning the characteristics of the causative agent, surveillance, and available prevention and control measures at a global level. Implications for Coxiella burnetii and Brucella spp. infections in domesticated goats in Southeast Asia are discussed.